Penegakan Hukum terhadap Tindak Pidana Tanpa Hak Menguasai Senjata Tajam dalam Aksi Unjuk Rasa Penolakan RUU KUHP - Imanuel Sembiring; Ediwarman Ediwarman; Marlina Marlina (Journal of Education, Humaniora and Social Sciences (JEHSS), 2021)
This paper aims to examine and analyze the rule of law, law enforcement and criminal policy against criminal acts without the right to control sharp weapons. To approach this problem, the theory of the legal system is used. The data were collected through interview guidelines and analyzed qualitatively. This study concludes that the rule of law regarding law enforcement against criminal acts without the right to control sharp weapons in demonstrations is regulated in Emergency Law Number 12 of 1951 in Article 2 paragraph (1), Law no. 9 of 1998 concerning Freedom to Express Opinions in Public in Article 16, Perkapolri No. 7 of 2012 concerning Procedures for the Implementation of Services, Security, and Handling of Public Opinion Cases in Article 8 letter j. Law enforcement against criminal acts without the right to control sharp weapons in demonstrations against the Criminal Code Bill at the Medan District Court is carried out through investigations, prosecutions and judges' decisions. The criminal law policy against people who carry sharp weapons in Medan City consists of a penal policy carried out by legally processing the perpetrators, followed by examining the defendants at trial. Non-penal policies as a preventive measure for criminal acts without the right to control sharp weapons are counseling, raids and community participation.